Hippocampal Oscillations in the Rodent Model of Schizophrenia Induced by Amygdala GABA Receptor Blockade - Lanre-Amos, Tope; Kocsis, Bernat (Frontiers in Psychiatry, 2010)
Brain oscillations are critical for cognitive processes, and their alterations in schizophrenia have been proposed to contribute to cognitive impairments. Network oscillations rely upon GABAergic interneurons, which also show characteristic changes in schizophrenia. The aim of this study was to examine the capability of hippocampal networks to generate oscillations in a rat model previously shown to reproduce the stereotypic structural alterations of the hippocampal interneuron circuit seen in schizophrenic patients. This model uses injection of GABA-A receptor antagonist picrotoxin into the basolateral amygdala which causes cell-type specific disruption of interneuron signaling in the hippocampus. We found that after such treatment, hippocampal theta rhythm was still present during REM sleep, locomotion, and exploration of novel environment and could be elicited under urethane anesthesia. Subtle changes in theta and gamma parameters were observed in both preparations; specifically in the stimulus intensity—theta frequency relationship under urethane and in divergent reactions of oscillations at the two major theta dipoles in freely moving rats. Thus, theta power in the CA1 region was generally enhanced as compared with deep theta dipole which decreased or did not change. The results indicate that pathologic reorganization of interneurons that follows the over-activation of the amygdala-hippocampal pathway, as shown for this model of schizophrenia, does not lead to destruction of the oscillatory circuit but changes the normal balance of rhythmic activity in its various compartments.